1984
DOI: 10.1002/ps.2780150506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the chitin synthesis inhibitor complex nikkomycin on oogenesis in the mite Tetranychus urticae

Abstract: Some effects of the chitin synthesis inhibitor complex nikkomycin on oogenesis in the two‐spotted spider mite Tetranychus urticae were demonstrated by means of electron microscopy. Four main effects were evident, depending on the oogenetic stages. Nuclear defects, observed in oogonia and primary oocytes, included a widened nuclear envelope, the intermembranous spaces of which were filled with electron‐dense material, and the occurrence of small electron‐dense agglomerations and altered nucleoli inside the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As far as the latter process is concerned, the Acari have only occasionally been investigated. Several studies have dealt with ticks (Diehl, 1970;Hecker and Aeschlimann, 1970;Brinton and Oliver, 1971;Diehl, et al, 1982) and spider mites (Tetranychidae) (Dittrich and Streibert, 1969;Mothes and Seitz, 1981;Mothes-Wagner, 1984; Mothes-Wagner and Seitz, 1984), but egg-shell formation in most of these publications has been only briefly mentioned. Similarly, the information on the fine structure of egg shell in mites has been presented only in a few cases: gamasid mites (Witalinski, 1977), ticks (Diehl, et al, 1981), and acarid mites (Mazzini and Baiocchi, 1983;Callaini and Mazzini, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…As far as the latter process is concerned, the Acari have only occasionally been investigated. Several studies have dealt with ticks (Diehl, 1970;Hecker and Aeschlimann, 1970;Brinton and Oliver, 1971;Diehl, et al, 1982) and spider mites (Tetranychidae) (Dittrich and Streibert, 1969;Mothes and Seitz, 1981;Mothes-Wagner, 1984; Mothes-Wagner and Seitz, 1984), but egg-shell formation in most of these publications has been only briefly mentioned. Similarly, the information on the fine structure of egg shell in mites has been presented only in a few cases: gamasid mites (Witalinski, 1977), ticks (Diehl, et al, 1981), and acarid mites (Mazzini and Baiocchi, 1983;Callaini and Mazzini, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…The results of the present study are in line with previous studies, which revealed that eggshell amalgamation occurs in two phases, and ds- PcCHS1 strongly down-regulates chitin synthesis. All of these effects led to the disturbance of egg deposition [ 34 ]. A significantly reduced egg laying rate in response to the inhibition of PcCHS1 has been previously reported in different pest species [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%